Balance hídrico acumulado positivo en las primeras 72 horas de estancia hospitalaria como factor predictor de letalidad en niños con shock séptico en el Hospital Regional Docente de Trujillo - Núñez Moreno, Lourdes Mercedes (2020)
Sepsis is a major cause of death and morbidity in children worldwide. It is estimated that, worldwide, approximately half of pediatric deaths are due to infection and 29%-40% of children eventually die from sepsis. Sepsis is a life-threatening organ dysfunction caused by dysregulated host response to infection. The critically ill patient has increased fluid retention secondary to increases in intravascular and third space volume, as well as decreased renal capacity to excrete excess fluid. Positive fluid balance > 10% of body weight has been associated with increased morbidity and mortality in patients with septic shock. This cumulative fluid balance is associated with the development of systemic and regional hypoperfusion and, subsequently, multiorgan failure. Septic shock is a pathological condition whose evolution can be ominous, which will depend on the prompt intervention by the health team in the first hours in which the patient is approached; in this sense, there is a growing interest in the use of indicators that allow the prognosis of these patients to be assessed as early as possible. At present, there is recent information that attributes prognostic character to excessive fluid intake during resuscitation of the patient with septic shock. The present project aims to determine whether positive cumulative fluid balance >10% of admission body weight in the first 72 hours of hospital stay is a predictor of lethality in children with septic shock.